Consideraciones de diseño de cimentaciones tipo pórtico para equipos dinámicos - González, David Leonardo (Escuela Colombiana de Ingeniería Julio Garavito, 2014)
The foundations of machines are a fundamental part of any industrial complex. This paper presents the main considerations and design criteria for projecting safe and efficient foundations. The difference with conventional foundations lies in the dynamic analysis that must be developed to ensure that the frequencies of the machine-foundation system are different from the normal operating frequency of the machine and that the amplitudes of the system are framed within the admissible limits. As a complement, this This work presents a practical example where the behavior of a gantry type foundation for a turbogenerator is studied, which is dimensioned and its analysis and design is carried out. The example is developed analytically and by finite elements using a computational tool of design. Finally, comparisons of the theoretical and experimental results were made with excellent approximations. The results obtained are shown sequentially to facilitate their understanding and the content is arranged to present to the reader the importance of the measurement of vibrations in the equipment-foundations system. The idea is that the reader understands the practical meaning of the frequencies and amplitudes in the analysis gantry type for dynamic equipment. The present work was justified because it has a practical value and educational relevance. In addition, strong foundations were established to familiarize the student with the design of dynamic equipment, showing that today the technology establishes better performance when performing mathematical models but always with the caution and aware that a good characterization of the input data must be obtained.

Las cimentaciones de máquinas son parte fundamental de todo complejoindustrial. En este trabajo se presentan las consideraciones principales y loscriterios de diseño para proyectar cimentaciones seguras y eficientes. Ladiferencia con las cimentaciones convencionales, radica en el análisis dinámicoque se debe desarrollar para garantizar que las frecuencias del sistema máquinafundación sean distintas de la frecuencia de operación normal de la máquina y quelas amplitudes del sistema se enmarquen dentro de los lÍmites admisibles.Como complemento, este trabajo presenta un ejemplo práctico donde se estudia elcomportamiento de una cimentación tipo pórtico para un turbogenerador, la cuales dimensionada y se realiza su análisis y diseño. El ejemplo es desarrolladoanalÍticamente y por elementos finitos utilizando una herramienta computacionalde diseño. Finalmente, se realizaron comparaciones de los resultados teóricos yexperimentales con excelentes aproximaciones. Los resultados obtenidos semuestran secuencialmente para facilitar su entendimiento y el contenido estáordenado para presentar al lector la importancia de la medición de las vibracionesen el sistema equipo-cimentación. La idea es que el lector comprenda elsignificado práctico de las frecuencias y amplitudes en el análisis decimentaciones tipo pórtico para equipos dinámicos.El presente trabajo se justificó por cuanto este posee un valor práctico y relevanciaeducativa. Además se establecieron bases fuertes para familiarizar al estudiantecon el diseño de equipos dinámicos, mostrando que hoy en dÍa la tecnologÍaestablece mejores rendimientos a la hora de realizar modelos matemáticos perosiempre con la precaución y consiente que se debe tener una buenacaracterización de los datos de entrada
Keywords: Análisis dinámico; Amplitud; Amortiguamiento; Cimentación tipo pórtico; Elementos finitos; Frecuencia; Masa; Resonancia; Vibraciones.; Dynamic analysis; Damping; Finite elements; Mass; Vibrations; Amplitude; Frequency; Gantry type foundation; Resonance